Customer Self-Congruity and Brand Image on Purchase Decision: The Role of Gender and Age as Control Variables - Endy Gunanto Marsasi; Mohamad Rizan; Sarah Barqiah; Yenni Kurnia Gusti (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
The impetus for this research is Generation Z's lack of understanding of social media marketing and brand image in relation to buying local products, because local brands are generally less successful. Self-congruence is new to assess consumer alignment with brands, which ultimately influences purchase decisions. The study's gap focuses on brand image, highlighting challenges consumers face in identifying with brands via social media. This study aims to show the impact of social media marketing on customer self-alignment, brand image, and purchase decision. The research data was collected by distributing questionnaires using a purposive sampling method to 217 gen Z participants who use local skincare and analyzed using SEM. The results show that all hypotheses influence each other by applying the self-expansion theory, where consumers will align themselves with brands from local products so that consumers will expand their self-concept and culminate in purchasing decisions. This study will also examine customer characteristics by gender and age as control variables that can be fully predicted. The findings of this study indicate a difference in gender, where women are more easily attracted to try than men. Younger consumers were found to prefer shopping online rather than physically, in contrast to older consumers.